A reconstruction of sea surface temperature variability in the southeastern Gulf of Mexico from 1734 to 2008 C.E. using cross‐dated Sr/Ca records from the coral Siderastrea siderea. (22nd May 2014) - DeLong, Kristine L.; Flannery, Jennifer A.; Poore, Richard Z.; Quinn, Terrence M.; Maupin, Christopher R.; Lin, Ke; Shen, Chuan‐Chou
Abstract This study uses skeletal variations in coral Sr/Ca from three Siderastrea siderea coral colonies within the Dry Tortugas National Park in the southeastern Gulf of Mexico (24°42′N, 82°48′W) to reconstruct monthly sea surface temperature (SST) variations from 1734 to 2008 Common Era (C.E.). Calibration and verification of the replicated coral Sr/Ca‐SST reconstruction with local, regional, and historical temperature records reveals that this proxy‐temperature relationship is stable back to 1879 C.E. The coral SST reconstruction contains robust interannual (~2.0°C) and multidecadal variability (~1.5°C) for the past 274 years, the latter of which does not covary with the Atlantic Multidecadal Oscillation. Winter SST extremes are more variable than summer SST extremes (±2.2°C versus ±1.6°C, 2σ) suggesting that Loop Current transport in the winter dominates variability on interannual and longer time scales. Summer SST maxima are increasing (+1.0°C for 274 years, σMC = ±0.5°C, 2σ), whereas winter SST minima contain no significant trend. Colder decades (~1.5°C) during the Little Ice Age (LIA) do not coincide with decades of sunspot minima. The coral SST reconstruction contains similar variability to temperature reconstructions from the northern Gulf of Mexico (planktic foraminifer Mg/Ca) and the Caribbean Sea (coral Sr/Ca) suggesting areal reductions in the Western Hemisphere Warm Pool during the LIA. Mean summer coral SST extremes post‐1985 C.E. (29.9°C) exceeds the long‐term summer average (29.2°C for 1734–2008 C.E.), yet the warming trend after 1985 C.E. (0.04°C for 24 years, σMC = ±0.5, 2σ) is not significant, whereas Caribbean coral Sr/Ca studies contain a warming trend for this interval.